Análisis de requerimientos para la implementación de un sistema informático para el departamento de estadística de la Federación Deportiva de Los Ríos - Gómez Jácome, Jorge Iván (2020)
Implement a computer system in The Rivers Provincial Sports Federation to systematically carry all the information regarding athletes (Personal, Educational, Medical, Psychological, Social data and their Sports results), this leads to statistics taking it away manually, thus being filed in folders and folders, in this way it is evident that in order to have access to all information requested by some authority of the institution or any particular request to the institution, it is necessary to resort to reviewing all the files that rest in the files, this leading to this required information taking from 48 hours to 1 week and also many times the information is not complete due to the fact that certain documents were lost or simply not there. In order to collect all the necessary information, the field methodology is used, once all the relevant information has been collected, it will be entered into the new statistical computer system and thus it will replace the way it is currently carried out, thus achieving that all Information required by any authority / employee of the institution or individual will obtain it immediately or up to 24 hours depending on the need, form and / or applicant.